Hot melt adhesive composition and laminate

CN117083362BActive Publication Date: 2026-11-03TOYOBO MC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280024060.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-25
Filing Date
2022-03-16
Publication Date
2026-11-03
Estimated Expiration
2042-03-16

AI Technical Summary

Technical Problem

In the existing technology, olefin resins have poor adhesion to polar resins, and the adhesives have poor operability, low productivity, and are difficult to meet the needs of automatic coating, and the bonding strength is insufficient.

Method used

A hot-melt adhesive composed of acid-modified polyolefin and copolyester in a specific ratio, with a melting point difference within 40°C, an acid value to hydroxyl value ratio in the range of 0.5 to 4.5, containing more than 70% copolyester, with added antioxidants and other additives, is prepared by high-temperature melt mixing using a twin-shaft extruder.

Benefits of technology

It achieves good adhesion between olefin and polar substrates, improves operability and productivity, enhances mechanical properties, and is suitable for automated coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004464487350000131
    Figure BDA0004464487350000131
  • Figure BDA0004464487350000141
    Figure BDA0004464487350000141
  • Figure BDA0004464487350000151
    Figure BDA0004464487350000151
Patent Text Reader

Abstract

The present application provides a hot melt adhesive composition containing an acid-modified polyolefin and a copolymer polyester, satisfying (1) to (5) below, (1) the copolymer polyester is composed of a dicarboxylic acid component and a diol component, and has a melting point (T1) in the range of 80 to 150°C measured by a differential scanning calorimeter (DSC), (2) the acid-modified polyolefin has a melting point (T2) in the range of 60 to 150°C measured by DSC, (3) |T1-T2|≤40°C, (4) when the acid value of the acid-modified polyolefin is AV (eq / ton) and the hydroxyl value of the copolymer polyester is OHV (eq / ton), 0.5≤AV / OHV≤4.5 is satisfied, and (5) when the total amount of the acid-modified polyolefin and the copolymer polyester is 100 mass%, the acid-modified polyolefin is contained in an amount of 5 to 40 mass% and the copolymer polyester is contained in an amount of 60 to 95 mass%, and when the total amount of the hot melt adhesive composition as a whole is 100 mass%, the total amount of the acid-modified polyolefin and the copolymer polyester is 70 mass% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a hot melt adhesive composition and a laminate bonded using the hot melt adhesive composition. Background Technology

[0002] Olefin resins such as polypropylene (PP) and propylene-α-olefin copolymers are widely used in various fields, primarily automobiles and home appliances, due to their low cost, light weight, and excellent strength, chemical resistance, and hydrolysis resistance. Especially in recent years, with rising fuel costs and a strong demand for lightweight vehicles, olefin resins have been widely discussed as a metal substitute. However, because these olefin resins are non-polar, it is difficult to achieve good adhesion to these molded products and films. To improve this, various methods have been tried, including chemical treatment with reagents, corona discharge treatment, plasma treatment, and flame treatment, to acidify the surface of olefin resins. However, these methods not only require specialized equipment, but their improvement in adhesion and coatability is still not entirely satisfactory.

[0003] Chlorinated polyolefins and acid-modified polyolefins have been developed as relatively simple methods to impart good paintability and adhesion to olefin resins. Since polyolefins are generally insoluble in solvents, methods are employed to reduce crystallinity and increase solubility through chlorination and copolymerization with α-olefins. Furthermore, since acid modification can also reduce crystallinity, resins with good solubility have been obtained through acid modification. However, these resins also suffer from low compatibility with polar resins and cannot achieve good adhesion to highly polar resins such as polyvinyl chloride (PVC) and polyethylene terephthalate.

[0004] Therefore, epoxy-based adhesives and urethane-based adhesives are used in the bonding of olefin resins and ester resins. These exhibit excellent mechanical properties due to the formation of three-dimensional crosslinks based on the reaction between the resin and the curing agent (e.g., Patent Document 1). Furthermore, a resin composition consisting of polyester and modified polyolefin is also disclosed (e.g., Patent Document 2).

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 4-323292

[0008] Patent Document 2: Japanese Patent Application Publication No. 5-86239 Summary of the Invention

[0009] The problem the invention aims to solve

[0010] However, the adhesive in Patent Document 1 is typically a two-component adhesive consisting of resin and curing agent. Problems include: requiring accurate weighing and mixing before use, resulting in poor operability. Furthermore, it gels quickly after mixing, limiting usable time to a few tens of minutes to a few hours, making it unsuitable for automated application using dispensers, and requiring the disposal of remaining components. Curing also takes several tens of minutes to several hours, leading to low productivity. Moreover, the resin composition in Patent Document 2 uses a polyester with amide bonds, resulting in a significant increase in melt viscosity and a decrease in adhesion due to hydrogen bonds between the amide bonds and between the amide bonds and the modified polyolefin.

[0011] The technical problem of the present invention is to provide a hot melt adhesive composition that improves operability and productivity, has good adhesion to olefin substrates such as polypropylene, good adhesion to highly polar substrates such as PVC and PET, and further has excellent mechanical properties.

[0012] Technical means to solve the problem

[0013] A hot melt adhesive composition containing acid-modified polyolefin and copolyester, satisfying the following (1) to (5).

[0014] (1) The copolyester is composed of dicarboxylic acid and diol components, and its melting point (T1) measured by differential scanning calorimetry (DSC) is in the range of 80 to 150°C.

[0015] (2) The melting point (T2) of acid-modified polyolefins, as measured by differential scanning calorimetry (DSC), is in the range of 60–150 °C.

[0016] (3)|T1-T2|≤40℃

[0017] (4) When the acid value of the acid-modified polyolefin is AV (eq / ton) and the hydroxyl value of the copolyester is OHV (eq / ton), the following condition is met: 0.5 ≤ AV / OHV ≤ 4.5

[0018] (5) When the total amount of acid-modified polyolefin and copolyester is 100% by mass, it contains 5-40% by mass of acid-modified polyolefin and 60-95% by mass of copolyester. When the total amount of the hot melt adhesive composition is 100% by mass, the total amount of acid-modified polyolefin and copolyester is 70% by mass or more.

[0019] The acid-modified polyolefin resin is preferably a maleic anhydride-modified polyolefin.

[0020] In addition, the polycarboxylic acid component of the copolyester contains both aromatic dicarboxylic acids and aliphatic dicarboxylic acids, and the alkylene glycol component is preferably a saturated aliphatic glycol.

[0021] A laminate of a polyvinyl chloride material and a polyolefin substrate bonded together using the hot melt adhesive composition described above.

[0022] The effects of the invention

[0023] The hot melt adhesive composition of the present invention uses specific copolyesters and acid-modified polyolefins in specific amounts, and has both non-polar and polar components, thus exhibiting good adhesion between different substrates (dissimilar substrates) such as olefin substrates like polypropylene and polar substrates like PVC and PET. Detailed Implementation

[0024] The present invention is described in detail below. The hot melt adhesive composition of the present invention contains acid-modified polyolefin and copolyester, and must satisfy the following (1) to (4).

[0025] <Hot melt adhesive composition that satisfies (1)>

[0026] (1) will be explained. The copolyester used in the hot melt adhesive composition of the present invention is composed of a dicarboxylic acid component and a diol component, and its melting point (T1) measured by differential scanning calorimetry (DSC) is in the range of 80 to 150°C. Preferably, it is 90 to 120°C, more preferably 95 to 115°C. When T1 is above 80°C, the heat resistance of the hot melt adhesive composition tends to become better. When T1 exceeds 150°C, more heat is applied when melting the hot melt adhesive composition, which has a negative impact on both economy and environment.

[0027] <Hot melt adhesive composition that satisfies (2)>

[0028] (2) will be explained. The melting point (T2) of the acid-modified polyolefin used in this invention, measured by differential scanning calorimetry (DSC), is in the range of 60–150°C. Preferably, it is 65–125°C, more preferably 70–110°C. When T2 is below 60°C, the heat resistance of the hot melt adhesive composition decreases. When T2 is above 150°C, more heat needs to be applied to melt the hot melt adhesive composition, thus having a negative impact on both the economy and the environment.

[0029] <Hot melt adhesive composition that satisfies (3)>

[0030] (3) will be explained. The hot melt adhesive composition used in this invention satisfies |T1-T2|≤40 (°C). Preferably, |T1-T2|≤30 (°C), more preferably |T1-T2|≤20 (°C). When |T1-T2| exceeds 40°C, when bonding by heating, only the low melting point component melts first, resulting in a decrease in the bonding strength with the polar substrate.

[0031] <Hot melt adhesive composition that satisfies (4)>

[0032] (4) will be explained. Let the acid value of the acid-modified polyolefin constituting the hot melt adhesive composition of the present invention be AV (eq / ton), and the hydroxyl value of the copolyester be OHV (eq / ton), satisfying 0.5 ≤ AV / OHV ≤ 4.5. Preferably, it is 0.8 ≤ AV / OHV ≤ 3.5, more preferably 1.0 ≤ AV / OHV ≤ 3.0. When 0.5 > AV / OHV, the proportion of hydroxyl groups in the polyester relative to the acid in the acid-modified polyolefin decreases, hydrogen bonds weaken, and melt viscosity decreases. When melt viscosity decreases, shear force cannot be applied when preparing the hot melt adhesive composition by melt mixing, the acid-modified polyolefin and polyester cannot achieve a good dispersion state, and the adhesion to the substrate decreases. When AV / OHV ≤ 4.5, the melt viscosity of the hot melt adhesive composition is not too high, resulting in good wettability to the substrate, especially good adhesion to polyvinyl chloride (PVC).

[0033] <Hot melt adhesive composition that satisfies (5)>

[0034] (5) will be explained. In the hot melt adhesive composition of the present invention, when the total amount of acid-modified polyolefin and copolyester is 100% by mass, it contains 5-40% by mass of acid-modified polyolefin and 60-95% by mass of copolyester. Preferably, it contains 20-40% by mass of acid-modified polyolefin and 60-80% by mass of copolyester. More preferably, it contains 25-35% by mass of acid-modified polyolefin and 65-75% by mass of copolyester. In compositions outside the above ranges, good adhesion to the two substrates cannot be obtained due to uneven polarity balance when bonding dissimilar substrates. Furthermore, when the composition of acid-modified polyolefin and copolyester meets the above ranges, and when the total amount of the hot melt adhesive composition is 100% by mass, the total amount of acid-modified polyolefin and copolyester needs to be 70% by mass or more. Preferably, it is 80% by mass or more, more preferably 90% by mass or more.

[0035] <Acid-modified polyolefins>

[0036] Examples of acid-modified polyolefins used as raw materials for the acid-modified polyolefins of this invention include polyethylene, polypropylene, ethylene-propylene copolymers, propylene-butene copolymers, and ethylene-propylene-butene copolymers. From the viewpoint of heat resistance and compatibility with copolyesters, it is preferable to select one or more from the group consisting of polypropylene, ethylene-propylene copolymers, and ethylene-propylene-butene copolymers (hereinafter also referred to as propylene-based polymers). The propylene content in the propylene-based polymer is preferably 50 mol% or more, more preferably 70 mol% or more. Furthermore, as acid-modified polyolefins, polyolefins copolymerized with unsaturated acids such as (meth)acrylates and (meth)acrylic acid, as well as alkyl esters of unsaturated acids, vinyl acetate, ethylene, propylene, and α-olefins can be used.

[0037] The acid-modified polyolefin used in this invention is preferably a product of graft polymerization (hereinafter also referred to as acid modification) of at least one of the unsaturated carboxylic acids with 3 to 10 carbon atoms and their anhydrides and esters. The weight of the grafted chains relative to the total weight of the acid-modified polyolefin (hereinafter also referred to as the acid modification amount) is preferably 0.5 to 10% by mass, more preferably 0.7 to 3% by mass. When the weight fraction of the grafted chains is outside the above range, the adhesion to the polyolefin substrate decreases.

[0038] Examples of unsaturated carboxylic acids with 3 to 10 carbon atoms, their anhydrides, and esters include: acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, and other unsaturated carboxylic acids; anhydrides of unsaturated carboxylic acids such as maleic anhydride, itaconic anhydride, and citraconic anhydride; and alkyl esters of unsaturated carboxylic acids such as methyl acrylate, methyl methacrylate, and dimethyl maleate. Among these, maleic acid, itaconic acid, and their anhydrides are preferred.

[0039] The graft polymerization used in manufacturing the acid-modified polyolefin of this invention can be carried out according to known methods, and the method is not particularly limited. For example, an organic peroxide can be added to a molten mixture of the polyolefin and the unsaturated carboxylic acid component to carry out graft polymerization. Alternatively, an organic peroxide can be added to a solution containing a mixture of the polyolefin and the unsaturated carboxylic acid component dissolved in a solvent such as toluene or xylene to carry out graft polymerization. When carrying out graft polymerization, it is preferable to avoid the introduction of air and oxygen, and it is preferable to carry it in an atmosphere of inactive gas such as nitrogen. Examples of the organic peroxide include acetyl peroxide sulfonylcyclohexane, benzoyl peroxide, dichlorobenzoyl peroxide, dicumyl peroxide, 2-tert-butyl peroxide, lauroyl peroxide, etc., and one or more of these can be used in combination.

[0040] The melt viscosity of the acid-modified polyolefin at 190°C is preferably 1,000 to 20,000 mPa·s, more preferably 2,000 to 15,000 mPa·s, and even more preferably 3,000 to 13,000 mPa·s. When the melt viscosity is 1,000 mPa·s or lower, the cohesive force is low, and the adhesive strength to the base material decreases; when the melt viscosity is 20,000 mPa·s or higher, the conformability to the base material decreases. Further, the melt viscosity of the copolyester at 190°C is preferably 220,000 mPa·s or lower, more preferably 200,000 mPa·s or lower. When it is 220,000 mPa·s or higher, the conformability to the base material decreases.

[0041] The melting point T1 of the acid-modified polyolefin is preferably 60°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher. In addition, it is preferably 150°C or lower, more preferably 140°C or lower, and even more preferably 130°C or lower. When the melting point of the acid-modified polyolefin is lower than 60°C, there is a concern that the adhesiveness will decrease significantly due to a temperature rise in the usage environment; when it exceeds 150°C, there is a concern that the olefin base material will melt during adhesion. Further, when the melting point of the copolyester is defined as T2, it is preferable to satisfy |T1-T2| ≤ 40 (°C). When |T1-T2| exceeds 40°C, when adhesion is performed by heating, only the low-melting-point component melts first, which may lead to a decrease in the adhesive strength to the polar base material.

[0042] The weight average molecular weight (Mw) of the acid-modified polyolefin is preferably 30,000 to 120,000, more preferably 40,000 to 110,000, and even more preferably 50,000 to 100,000. In addition, the number average molecular weight (Mn) is preferably 10,000 to 70,000, more preferably 15,000 to 60,000, and even more preferably 20,000 to 55,000. Further, the molecular weight distribution (Mw / Mn) is preferably 3 or less, more preferably 2.8 or less. By using the acid-modified polyolefin in the above range, the compatibility with the copolyester increases, and the adhesiveness of the hot-melt adhesive composition can be made favorable.

[0043] The AV of the acid-modified polyolefin is preferably 50 to 500, more preferably 100 to 400, and even more preferably 150 to 300. When 50 > AV, the adhesion force of the acid-modified polyolefin to the polyolefin base material is low, and the adhesive strength decreases. When 500 < AV, the cohesive force of the acid-modified polyolefin becomes small, and the adhesive strength decreases.

[0044] <Copolyester>

[0045] The copolyester used in the present invention can be obtained by, for example, subjecting a dicarboxylic acid component such as a dicarboxylic acid or its acid anhydride and alkyl ester, and a diol component to dehydration condensation or dealcoholization condensation.

[0046] Examples of the compound that forms the dicarboxylic acid component include aromatic dibasic acids such as terephthalic acid, isophthalic acid, phthalic anhydride, 1,2-naphthalenedicarboxylic acid and 1,6-naphthalenedicarboxylic acid, or aliphatic dicarboxylic acids and alicyclic dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanoic acid, dimer acid, hydrogenated dimer acid, dodecenylsuccinic anhydride, fumaric acid, dodecanedioic acid, 1,2-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, maleic acid, maleic anhydride, itaconic acid and citraconic acid.

[0047] When the total dicarboxylic acid component is taken as 100 mol%, the content of the aromatic dicarboxylic acid is preferably 40 mol% or more, more preferably 45 mol% or more, and still more preferably 50 mol% or more. The upper limit is not particularly limited, and it may be 100 mol%, but it is preferably 95 mol% or less, more preferably 90 mol% or less. The content of the aliphatic dicarboxylic acid and the alicyclic dicarboxylic acid is preferably 60 mol% or less, more preferably 55 mol% or less, and still more preferably 50 mol% or less. When the amount of the aromatic dicarboxylic acid is too small and the amounts of the aliphatic dicarboxylic acid and the alicyclic dicarboxylic acid are too large, the adhesiveness and heat resistance of the hot-melt adhesive composition may decrease.

[0048] The OHV of the copolyester is preferably 20 to 200, more preferably 30 to 170, and still more preferably 50 to 150. When OHV is less than 30, the interaction with the acid-modified polyolefin becomes small, and poor dispersion occurs during melt-kneading. When OHV is more than 150, the adhesion to the polyolefin base material decreases when the adhesive layer is bonded.

[0049] Other diol components include: ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 2,2-dimethyl-3-hydroxypropyl-2',2'-dimethyl-3'-hydroxypropionate, 2-(n-butyl)-2-ethyl-1,3-propanediol, 3-ethyl-1,5-pentanediol, 3-propyl-1,5-pentanediol, 2,2-diethyl-1,3-propanediol, 3-octyl... Aliphatic diols such as 1,5-pentanediol, 1,3-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxyethyl)cyclohexane, 1,4-bis(hydroxypropyl)cyclohexane, 1,4-bis(hydroxymethoxy)cyclohexane, 1,4-bis(hydroxyethoxy)cyclohexane, 2,2-bis(4-hydroxymethoxycyclohexyl)propane, 2,2-bis(4-hydroxyethoxycyclohexyl)propane, bis(4-hydroxycyclohexyl)methane, 2,2-bis(4-hydroxycyclohexyl)propane, 3(4),8(9)-tricyclo[5.2.1.02,6]decanediethanol and other alicyclic diols or ethylene oxide adducts and propylene oxide adducts of bisphenol A and other aromatic diols, or polyethylene glycol, polypropylene glycol, polytrimethylene ether glycol, etc. You can use one or more of these.

[0050] Furthermore, for the copolyester used in this invention, a portion of the dicarboxylic acid component may be replaced with a carboxylic acid with three or more functionalities, or a portion of the diol component may be replaced with a polyol with three or more functionalities before copolymerization. Examples of these compounds with three or more functionalities include: trimellitic acid, pyromellitic acid, benzophenone tetracarboxylic acid, biphenyl tetracarboxylic acid, ethylene glycol bis(triphenyltriglyceride), glycerol trimellitic anhydride ester, and other polycarboxylic acids or their anhydrides, trimethylolpropane, pentaerythritol, glycerol, polyglycerol, and other polyfunctional diols.

[0051] Furthermore, the copolyester used in this invention can also be copolymerized or added to glycolic acid, lactones, lactide, (poly)carbonate, or added to anhydride and copolymerized with glycolic acid.

[0052] The copolyester used in this invention is preferably a polyester whose main chain does not contain amide bonds. The amount of amide bonds in the main chain of the copolyester is preferably less than 5 × 10⁻⁶ per 100g of copolyester. -4 Moles. More preferably 1 × 10 -4 The mole, more preferably 1 × 10 -5 Less than 10 moles. Amide bonds contain 5 × 10⁻⁶.-4 When the molar concentration is above a certain level, there is a concern that the melt viscosity will increase significantly and the adhesion will decrease due to hydrogen bonds between amide bonds in the copolyester and hydrogen bonds between amide bonds and the acid-modified portion of the acid-modified polyolefin.

[0053] The melt viscosity of the copolyester at 190°C is preferably below 220,000 mPa●s, more preferably below 200,000 mPa●s, and at 220,000 mPa●s or below, it exhibits good adhesion to the substrate.

[0054] The melting point T2 of the copolyester is preferably 80°C or higher, more preferably 85°C or higher, and even more preferably 90°C or higher. Furthermore, it is preferably below 150°C, more preferably below 130°C, and even more preferably below 120°C. When T2 is below 80°C, there is a concern that the adhesion may significantly decrease due to the increase in ambient temperature; when it exceeds 150°C, there is a concern that the olefin substrate may melt during bonding.

[0055] Whether the copolyester is crystalline or amorphous has no effect, but crystalline copolyester is preferred. When it is a crystalline copolyester, the increase in resin strength due to crystallization can be predicted to lead to an increase in adhesive strength.

[0056] Furthermore, it is preferable to add an antioxidant to the hot melt adhesive composition of the present invention. Preferred antioxidants include hindered phenolic antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, amine-based antioxidants, etc., and one or more of these may be used. In particular, the combination of hindered phenolic antioxidants with other antioxidants is very effective. In addition, it is preferable to add stabilizers such as heat aging agents, copper inhibitors, antistatic agents, light stabilizers, and ultraviolet absorbers. Especially from the viewpoint of efficiently capturing free radicals, it is preferable to use phenolic antioxidants containing phosphorus atoms in their molecules. Furthermore, nucleating agents, flame retardants, etc., may also be added.

[0057] Examples of hindered phenolic antioxidants and stabilizers include: 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,1,3-tris(4-hydroxy-2-methyl-5-tert-butylphenyl)butane, 1,1-di(3-tert-butyl-6-methyl-4-hydroxyphenyl)butane, 3,5-di(1,1-dimethylethyl)-4-hydroxyphenylpropionic acid, and pentaerythritol tetratetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)] [3-(1,1-dimethylethyl)-4-hydroxy-5-methylphenylpropionic acid], 3,9-bis[1,1-dimethyl-2-[(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, 1,3,5-trimethyl-2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)benzene, thiodiethylenebis[3- (3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 3,3',3”,5,5'5”-hexyl-tert-butyl-a,a',a”-(trimethylbenzene-2,4,6triyl)tri-p-cresol, diethyl[[3,5-bis[1 [1-Dimethylethyl]-4-hydroxyphenyl]methyl]phosphate, 4,4'-butylenebis(3-methyl-6-tert-butylphenol), 2'3-bis[[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionyl]]propionylhydrazine, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4-8,10-tetraoxaspiro[5.5]undecane, etc.

[0058] Examples of phosphorus-based antioxidants and stabilizers include: 3,9-di(p-nonylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosspiro[5.5]undecane, 3,9-di(octadecoxy)-2,4,8,10-tetraoxa-3,9-diphosspiro[5.5]undecane, tris(mononophenyl)phosphite, triphenoxyphosphine, isodeyl phosphite, isodeylphenyl phosphite, diphenyl-2-ethylhexyl phosphite, dinonylphenyl di(nonylphenyl) phosphate, 1,1,3-tris(2-methyl-4-di(tetrazyl)phosphite-5-tert-butylphenyl)butane, tris(2,4-di-tert-butylphenyl)phosphite, and pentaerythritol. Bis(2,4-di-tert-butylphenyl) phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)2-ethylhexyl phosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis[2,4-bis[1,1-dimethylethyl]-6-methylphenyl]ethyl phosphite, 6-[3-(3-tert-butyl-4-hydroxy-5-methyl)propoxy]-2,4,8,10-tetra-tert-butyl-dibenzo[d,f][1,3,2]-dioxaphosphorus, tetra(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diylbisphosphonate, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, etc.

[0059] Examples of sulfur-based antioxidants and stabilizers include: 4,4'-thiobis[2-tert-butyl-5-methylphenyl]bis[3-(dodecylthio)propionate], thiobis[2-(1,1-dimethylethyl)-5-methyl-4,1-phenylene]bis[3-(tetradecylthio)propionate], pentaerythritol tetra(3-n-dodecylthiopropionate), thiodipropionate bis(tridecyl) ester, 3,3'-thiodipropionate bisdodecyl ester, 3,3'-thiodipropionate bisoctadecyl ester, 4,6-bis(octylthiomethyl)-o-cresol, and 4,4'-thiobis(3-methyl-6-tert-butylphenol), etc.

[0060] Examples of amine-based antioxidants and stabilizers include: 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, 2',3-bis[[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionyl]]propionylhydrazine, N,N'-di-2-naphthyl-p-phenylenediamine, N-phenyl-N'-4,4'-thiobis(2-tert-butyl-5-methylphenol), and 2,2-bis[3-(dodecylthio)propionyloxymethyl]-1,3-propanediol bis[3-(dodecylthio)propionate].

[0061] The amount of antioxidant added relative to the overall adhesive composition is preferably 0.1% by mass to 5% by mass. Below 0.1% by mass, the effect of resisting heat degradation will be deteriorated. Above 5% by mass, there may be negative effects on adhesion and other properties.

[0062] For the hot melt adhesive composition of the present invention, other resins such as epoxy resin, polyamide resin, polyolefin resin, polycarbonate resin, acrylic resin, ethylene-vinyl acetate resin, and phenolic resin may be mixed in without impairing the performance of the present invention, which can improve adhesion, flexibility, durability, etc. The amount of other resins mixed is preferably less than 5% by mass of the total amount of the hot melt adhesive composition. Furthermore, mixing isocyanate compounds, curing agents such as melamine, fillers such as talc or mica, pigments such as carbon black and titanium dioxide, flame retardants such as antimony trioxide and brominated polystyrene does not have an effect.

[0063] For the hot melt adhesive composition of the present invention, tackifiers such as rosin and terpenes may also be mixed in to improve adhesion. The mixing amount is preferably less than 5% by mass of the total amount of the hot melt adhesive composition.

[0064] The method for preparing the hot melt adhesive composition of the present invention is not particularly limited. Examples include: melt mixing using an extruder such as a uniaxial extruder or a biaxial extruder; obtaining a molded article directly after melt mixing using a particle mixing molding machine; adding an acid-modified polyolefin before polymerization of the copolyester and then mixing; and mixing the two in a solution. However, the method of using a biaxial extruder, which can apply high shear stress, is particularly preferred. When using a biaxial extruder, melt mixing is preferably performed at a high temperature higher than the melting point of the acid-modified polyolefin and the copolyester used, specifically preferably at 150 to 300°C.

[0065] <Substrate>

[0066] As the polar substrate used in this invention, polyethylene terephthalate (PET), polyvinyl chloride (PVC), and other similar substrates can be used. Furthermore, as the polyolefin substrate, there are no particular limitations, and polyethylene (PE), polypropylene (PP), and other similar substrates can be used. Among these, a combination of PVC and PP is preferred.

[0067] <Layered Body>

[0068] The laminate of the present invention is a three-layer laminate (polar substrate / hot melt adhesive composition layer / polyolefin substrate) formed by laminating a polar substrate and a polyolefin substrate with a hot melt adhesive composition. The laminate can be obtained, for example, by laminating or coating a hot melt adhesive composition onto a polyester substrate (or polyolefin substrate), and further by sandwiching and hot-pressing the polyolefin substrate (or polyester substrate) together. The thickness of the hot melt adhesive composition layer in the laminate is preferably 5–200 μm, more preferably 10–100 μm, and even more preferably 15–50 μm. If the thickness is too thin, sufficient adhesive performance cannot be obtained; if the thickness is too thick, production efficiency decreases.

[0069] [Example]

[0070] The present invention is further described in detail below with reference to embodiments. However, the present invention is not limited to the embodiments. It should be noted that in the embodiments and comparative examples, a single "part" means parts by mass, and "%" means percentage by mass.

[0071] <<Evaluation Methods for Resin and Hot Melt Adhesive Compositions>>

[0072] <Composition Ratio>

[0073] The sample (copolyester or acid-modified polyolefin) was dissolved in chloroform-d and analyzed by 1H-NMR using a Varian Gemini-200 nuclear magnetic resonance analyzer (NMR) to determine the composition ratio.

[0074] <Acid Value (AV) of Acid-Modified Polyolefins>

[0075] The acid value (eq / ton) of the acid-modified polyolefin in this invention is expressed as the equivalent (eq / ton) of 1 ton of resin, calculated using FT-IR (manufactured by Shimadzu Corporation, FT-IR8200PC) and utilizing the absorbance (I) of the stretching peak (1780 cm⁻¹) of the carbonyl group (C=O) of maleic anhydride, the absorbance (II) of the isotactic peak (840 cm⁻¹), and a factor (f) obtained by a calibration curve based on a chloroform solution of maleic anhydride (manufactured by Tokyo Kasei).

[0076] Acid value = [Absorbance (I) / Absorbance (II) × (f) / Molecular weight of maleic anhydride × 2 × 10⁴]

[0077] Molecular weight of maleic anhydride: 98.06

[0078] <Hydroxy value (OHV) of copolyester>

[0079] The hydroxyl value of the copolyester in this invention is obtained according to the following steps: 50g of copolyester is dissolved in 120g of hot chloroform, 70g of 4,4-diphenylmethane diisocyanate is added, and the reaction is carried out at 70°C for 2 hours. Then, the concentration of residual isocyanate groups in the reaction solution is determined by titration to obtain the hydroxyl value (eq / ton) of the copolyester.

[0080] Melt viscosity

[0081] In a capillary rheometer (CFT-500C model) manufactured by Shimadzu Corporation, a resin sample (copolyester or acid-modified polyolefin) dried to a moisture content of less than 0.1% was filled into a hopper in the center of a heating element set to 190°C. After filling, pressure (4.9 MPa) was applied to the sample via a feed rod, and the molten sample was extruded through a die (orifice diameter: 0.5 mm, thickness: 20 mm) at the bottom of the hopper. The distance and time of feed rod descent were recorded, and the melt viscosity (mPa·s) was calculated.

[0082] <Weight-average molecular weight (Mw), Number-average molecular weight (Mn)>

[0083] In this invention, Mw and Mn are values ​​measured using a gel permeation chromatograph manufactured by Waters Corporation, Japan, Alliancee 2695 (hereinafter also referred to as GPC; standard material: polystyrene resin; mobile phase: tetrahydrofuran; chromatographic column: Shodex KF-806+KF-803; column temperature: 40℃; flow rate: 1.0 ml / min; detector: photodiode matrix detector (wavelength 254 nm = ultraviolet light)).

[0084] Melting point

[0085] In a differential scanning calorimeter (DSC220 model) manufactured by Seiko Electronics, 5 mg of the test sample (copolyester or acid-modified polyolefin) was placed in an aluminum pan, sealed with the lid, and kept at 250°C for 5 minutes at a time to allow the sample to completely melt. Afterward, it was rapidly cooled with liquid nitrogen, and then heated from -150°C to 250°C at a rate of 20°C / min. The melting point was then determined. The melting point was determined from the maximum absorption peak of the heat of fusion in the obtained thermogram.

[0086] <Preparation of Sheet Samples of Hot Melt Adhesive Compositions>

[0087] Using a benchtop test press SA-302 manufactured by Tester Industries, a sheet sample of hot melt adhesive composition with a thickness of 20 μm was formed at 160°C, maintaining a pressure of 20 MPa for 10 seconds.

[0088] <Adhesion Strength Evaluation>

[0089] A sheet sample was clamped between a PVC film (BONLEX BE, 50 μm thick) manufactured by Takiron-CI and a polypropylene sheet (2.5 mm thick) manufactured by Test Panel Co., Ltd. The sample for adhesive strength testing was formed by using an IMC-0800 heat-sealing tester from Imoto Manufacturing Co., Ltd., at 140°C and a constant pressure of 0.1 MPa for 120 seconds. The adhesive strength test sample was then cut to a 10 mm wide piece. The PVC film of the adhesive strength test sample was clamped on the upper jaw of a tensile testing machine manufactured by Shimadzu Corporation, and the polypropylene sheet was clamped on the lower jaw. The sample was stretched vertically at 50 mm / min using an Autograph AGX-V at 23°C and 60% Rh to determine the 180° peel strength. The adhesive strength was evaluated based on the measured values ​​and a comprehensive assessment.

[0090] (Overall Evaluation)

[0091] ○: The hot melt adhesive composition undergoes cohesive failure and the peel strength is above 15 N / 10 mm.

[0092] △: (1) The hot melt adhesive composition peels off from the interface of the polypropylene sheet or PVC film with a peel strength of 10 N / 10 mm or more, or (2) The hot melt adhesive composition undergoes cohesive failure with a peel strength of 10 N / 10 mm or more but less than 15 N / 10 mm.

[0093] ×: Peel strength is less than 10N / 10mm.

[0094] <<Manufacturing Examples and Embodiments>>

[0095] Example of manufacturing acid-modified polyolefin (a)

[0096] 100 parts by weight of crystalline polypropylene (polyolefin resin 1), 8 parts by weight of maleic anhydride, 2 parts by weight of dicumyl peroxide, and 150 parts by weight of toluene were added to a high-pressure reactor equipped with a stirrer. After sealing, nitrogen purging was performed for 5 minutes. Then, the reaction was carried out at 140°C for 5 hours while heating and stirring. Upon completion of the reaction, the reaction solution was added to a large amount of methyl ethyl ketone, causing resin to precipitate. The precipitated resin was removed, further washed several times with methyl ethyl ketone, and dried to obtain acid-modified polyolefin (a). Its composition and properties are shown in Table 1.

[0097] Manufacturing examples of acid-modified polyolefins (b) to (f)

[0098] Similar to the acid-modified polyolefin (a) above, acid-modified polyolefins (b) to (e) were prepared by changing the type of polyolefin resin being modified. The composition and properties of each acid-modified polyolefin are shown in Table 1.

[0099] [Table 1]

[0100]

[0101] Polyolefin resin 1: Propylene-butene copolymer (70 / 30 molar ratio) (weight average molecular weight 230,000)

[0102] Polyolefin resin 2: propylene-butene copolymer (=90 / 10 (molar ratio)) (weight average molecular weight 180,000)

[0103] Polyolefin resin 3: Propylene-ethylene-butene copolymer (70 / 10 / 20 molar ratio) (weight average molecular weight 170,000)

[0104] Manufacturing example of copolyester (A)

[0105] 30 parts by mass of terephthalic acid, 20 parts by mass of isophthalic acid, 50 parts by mass of adipic acid, 100 parts by mass of 1,4-butanediol, and 0.25 parts by mass of tetrabutyl titanate were added to a reaction vessel equipped with a stirrer, thermometer, and distillation cooler. An esterification reaction was carried out at 170–220°C for 2 hours. After the esterification reaction was completed, 0.5 parts by mass of the hindered phenolic antioxidant "Irganox (registered trademark) 1330" (manufactured by BASF Japan) was added, and the temperature was raised to 255°C. Simultaneously, the pressure in the system was slowly reduced, decreasing to 665 Pa at 255°C for 60 minutes. Then, a polycondensation reaction was further carried out at 133 Pa for 30 minutes to obtain polyester resin (A). The melting point of this polyester resin (A) is 110°C, and the melt viscosity at 190°C is 180,000 mPa·s.

[0106] Manufacturing examples of copolyesters (B) to (D)

[0107] Similar to the copolyester (A) described above, copolyester resins (B) to (D) were prepared by changing the dicarboxylic acid and diol components. The properties of each resin are shown in Table 2.

[0108] [Table 2]

[0109]

[0110] TPA: Terephthalic acid

[0111] IPA: Isophthalic acid

[0112] AA: Adipic acid

[0113] EG: Ethylene glycol

[0114] BD: 1,4-Butanediol

[0115] PTMG1000: Polytetramethylene ether glycol (number average molecular weight 1000)

[0116] Example 1

[0117] Hot melt adhesive composition (1)

[0118] A hot melt adhesive composition (1) was prepared by adding 30 parts by weight of the acid-modified polyolefin (a) as an acid-modified polyolefin and 70 parts by weight of the copolyester (A) as a copolyester, and by melt mixing at 190°C using a biaxial extruder. The adhesive strength, when measured using the above method, was 20 N / cm. The composition and properties are shown in Table 3.

[0119] Examples 2-9, Comparative Examples 1-8

[0120] Examples of manufacturing hot melt adhesive compositions 2-17

[0121] Hot melt adhesive compositions 2 to 17 were prepared according to the combination of Tables 3 and 4, using the same method as in Manufacturing Example 1. The adhesive strength was measured using the method described above. The composition and properties are shown in Tables 3 and 4.

[0122]

[0123]

[0124] Examples 1-9 meet the requirements of this invention and exhibit good adhesive strength. Comparative Example 1, containing more than 95% by mass of copolyester, is outside the scope of this invention, resulting in lower adhesion to PP film. Comparative Example 2, containing more than 50% by mass of acid-modified polyolefin, is outside the scope of this invention, resulting in lower adhesion to PVC film. Comparative Example 3, with an AV / OHV ratio of 4.5 or higher, is outside the scope of this invention, resulting in lower adhesion to both PP and PVC films. Comparative Example 4, with |T1-T2| > 40, exhibits lower adhesion due to uneven dispersion of the adhesive layer. Comparative Example 5, lacking acid-modified polyolefin, exhibits lower adhesion to PP film. Comparative Example 6, lacking copolyester, exhibits lower adhesion to PVC film. Comparative Example 7, using unmodified polyolefin instead of acid-modified polyolefin, exhibits lower adhesion to PP substrate. When the total amount of the hot melt adhesive composition is 100% by mass, the total amount of acid-modified polyolefin and copolyester in Comparative Example 8 is less than 70% by mass, so the adhesion is lower.

Claims

1. A hot melt adhesive composition containing an acid-modified polyolefin and a copolyester, satisfying the following (1) to (5), (1) The copolyester is composed of dicarboxylic acid and diol components, and its melting point T1, measured by differential scanning calorimetry (DSC), is in the range of 80–150 °C. (2) The melting point T2 of acid-modified polyolefins, as measured by differential scanning calorimetry (DSC), is in the range of 60–150 °C. (3) |T1-T2|≤40℃ (4) Assuming the acid value of the acid-modified polyolefin is AV and the hydroxyl value of the copolyester is OHV, the following conditions must be met: 0.5 ≤ AV / OHV ≤ 3.5, where the units of AV and OHV are both eq / ton. (5) When the total amount of acid-modified polyolefin and copolyester is 100% by mass, it contains 5 to 40% by mass of acid-modified polyolefin, and when the total amount of the hot melt adhesive composition is 100% by mass, the total amount of acid-modified polyolefin and copolyester is 70% by mass or more.

2. The hot melt adhesive composition according to claim 1, wherein, The acid-modified polyolefin resin is a maleic anhydride-modified polyolefin.

3. The hot melt adhesive composition according to claim 1 or 2, wherein, The dicarboxylic acid component of the copolyester contains both aromatic dicarboxylic acids and aliphatic dicarboxylic acids, while the alkylene glycol component is a saturated aliphatic glycol.

4. A laminate of a polyvinyl chloride material and a polyolefin substrate bonded together using the hot melt adhesive composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Aqueous urethane-based two liquid type adhesive and emulsion as main agent thereof

    JP1992323292A

  • Resin composition and multilayered structure using the same

    JP1993086239A

  • Hot-melt adhesive composition

    JP2017193699A